Case Study : Little Caliphs International Sdn Bhd / Nur Fatimah Mohd Yusoff - Mohd Yusoff, Nur Fatimah (2021)
Technology Entrepreneurship (ENT600) subject offer stimulation for the student to apply the technology solution in a real-life situation. In order to complete this task, I choose Little Caliphs International Sdn Bhd. as my case study to assist the company in facing their problems. Little Caliphs International Sdn Bhd. is one of the famous private kindergarten in Malaysia. This kindergarten has more than 400 branches in Malaysia and two branches in Indonesia. The problems faced by this kindergarten company are when fees are not same for each branch. Besides, the teachers always faced problem when most of the time students lost or inadvertently switched their things with friends even though parents have tagged the child’s things. The others problem is when parents does not convince with Phonic method that had been used by Little Caliphs kindergarten. From the above problem, I come out with a new solution to help Little Caliph kindergarten to solve their problems. The idea is to use the technological innovation that will help the company from time to time. Thus, in this report, I will explain in details about the idea to help Little Caliphs International Sdn Bhd. with that technology innovation that can ease their work later on.